Puritanism Islam in Indonesia - ., Alhamuddin; Satria Hamdani, Fahmi Fatwa Rosyadi; Irwansyah, Shindu; Alifudin, Muhammad; Murniati, Andi; Murniati, Andi; In’ami, Moh (KnE Social Sciences, 2023)
Salafism is a transnational Islamic movement that has spread worldwide, including in Indonesia. Etymologically, the term ”salaf” refers to the past or what occurred in previous times (Ma’luf 1986: 346). In addition to ”salaf,” the words ”salafiah” and ”salafi” (plural: ”salafiyun”) are widely used by scholars. ”Salafiah” refers to the teachings of the pious ancestors (”salaf al saleh”), while ”salafi” refers to the followers of these teachings (al-Thalibi 2006: 8). Currently, Salafism has evolved into an Islamic school of thought that regards true Islam as being attained only through imitating the interpretations and practices of the pious predecessors (salaf al salih) (al Bouty 1998: 9). The salaf al salih is considered an exemplary model of Islam. The spread of Salafism with the aim of purifying Islamic teachings and practices is referred to as the Salafi movement. Some scholars argue that Wahhabism in Saudi Arabia is another name for Salafism, as it can be traced genealogically from the salaf al salih—Ibn Taymiyya—Muhammad ibn Abd al Wahhab—and some prominent scholars from Saudi Arabia and Yemen. This research will focus on various aspects of Salafism, including its spread, da’wah strategies, and how its beliefs are presented in a manner that is appealing and accepted by people. The study follows an interpretive paradigm and utilizes the phenomenological approach to address the research problem. The data for this study will be collected from key figures and members of the Salafi movement in Wakatobi, as well as from local clerics, government officials, and relevant documents related to the research problem. There are at least three methods for collecting the data that we use in this study. Keywords: Puritanism, Islam, spread, movement, Salafiyah